JURASSIC PALEOGEOGRAPHY OF THE PIENINY AND OUTER CARPATHIAN BASINS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Jurassic history of the Pieniny/Outer Carpathian basins reflects the evolution of the Circum-Tethyan area, especially its Alpine Tethys part. The Alpine Tethys that is Ligurian, Penninic Oceans and Pieniny/Magura Basin constitute the extension of the Central Atlantic system. The synrift stage lasted in the Pieniny/Magura Basin from late Early Jurassic to Tithonian (the Magura Unit constitutes the southernmost part of the Outer Flysch Carpathians). The Pieniny rift opened during Pliensbachian – Aalenian. The central Atlantic and Alpine Tethys went into a drifting stage during the Middle Jurassic. The Late Jurassic (Oxfordian-Kimmeridgian) history of the Pieniny/Magura Basin reflects strongest facial differentiation within sedimentary basin where mixed siliceous-carbonate sedimentation took place. Greatest deepening effect is indicated by widespread Oxfordian radiolarites, which occur in the all basinal successions, whereas the shallowest zone is completely devoid of siliceous intercalations at that time (sedimentation from Ammonitico Rosso facies up to coral reef limestone). The southern part of the North European Platform, north from the Pieniny/Magura realm, started to be rifted during Late Jurassic time and Silesian Basin in the Outer Western Carpathians and Sinaia Basin in the Eastern Carpathians, with black, mainly redeposited marls have been created. The outer sub-basins were differentiated during the latest (Hauterivian-Barremian) phase of basinal development. The connection of Silesian Basin with Sinaia and Southern Carpathian Severin areas suggests the NW-SE direction of the basinal axis while the orientation of the Pieniny Klippen Belt/Magura Basin was SW-NE so, two Outer Carpathian perpendicular directions are possible within the basins. Major reorganization happened during the Tithonian-Berriasian time. It was reflected by both paleoceanographical and paleoclimatical changes. The Neo-Cimmerian tectonic events as well as main phase of the Outer Carpathian basins opening is connected with this reorganization.